Risk and prognostic factors for diarrheal disease in Brazilian infants: a special case-control design application Fatores de risco e prognósticos para diarréia entre crianças brasileiras: uma aplicação especial do delineamento de casos e controles - Sandra Costa Fuchs; Cesar Gomes Victora (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2002)
The aim of this study was to examine the effect of demographic, socioeconomic, environmental, maternal reproductive, dietary, and nutritional variables on diarrhea risk and prognosis using a hierarchical framework. A case-control study of children aged 0-23 months in Greater Metropolitan Porto Alegre was conducted during the peak season for diarrhea in 1987-1988. Three groups were investigated, with 192 children each. The first group included hospitalized children with an episode of acute diarrhea complicated by moderate to severe dehydration. The second group included children with acute mild diarrhea without signs of dehydration who were identified in the same neighborhood as hospitalized cases. The third group consisted of controls without diarrhea. Mothers were interviewed by trained interviewers using a standardized questionnaire. Data analysis included a hierarchical approach to control for confounding, using conditional logistic regression. Comparison of the three groups aimed to identify risk factors for diarrhea complicated by dehydration, prognostic factors for dehydration, and risk factors for mild diarrhea. Low birth weight, stunting, and lack or breastfeeding acted simultaneously as risk and prognostic factors for diarrhea. O objetivo deste estudo foi examinar o efeito de variáveis demográficas, sócio-econômicas, ambientais, reprodutivas maternas, dietéticas e nutricionais sobre o risco e o prognóstico de diarréia usando análise hierarquizada. Um estudo de caso-controle incluindo crianças entre 0-23 meses de idade, residentes na área metropolitana de Porto Alegre, foi realizado durante os meses de verão de 1987-88. Investigaram-se três grupos de 192 crianças, incluindo as hospitalizadas com um episódio agudo de diarréia e desidratação moderada a grave; as crianças com diarréia aguda leve e sem desidratação, identificadas na vizinhança dos casos, assim como crianças sem diarréia. Entrevistas padronizadas foram realizadas por entrevistadoras treinadas. Utilizou-se análise hierarquizada no controle de fatores de confusão. Calcularam-se razões de odds e intervalos de confiança de 95% através de regressão logística condicional. O emparelhamento de diferentes combinações de casos e controles permitiu invetigar fatores de risco para diarréia grave, fatores prognósticos e fatores de risco para diarréia leve. Baixo peso de nascimento, déficit altura-idade e ausência de aleitamento materno foram simultaneamente fatores de risco e prognóstico para diarréia.